STUDY OF ANTIATHEROSCLEROTIC AND ENDOTHELIOPROTECTIVE ACTIVITY OF PEPTIDE AGONISTS OF EPOR/CD131 HETERORECEPTOR - Olesya A. Puchenkova; Sergey V. Nadezhdin; Vladislav O. Soldatov; Maxim A. Zhuchenko; Diana S. Korshunova; Marina V. Kubekina; Evgeny N. Korshunov; Liliya V. Korokina; Polina A. Golubinskaya; Aleksandr L. Kulikov; Vladimir V. Gureev; Vladimir M. Pokrovskiy; et al. (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
Introduction. The drugs affecting a mitochondrial dysfunction, oxidative stresses, apoptosis and inflammation of the vascular wall, have a high potential for the prevention and treatment of atherosclerotic lesions. In this regard, the use of EPOR/CD131 heteroreceptor agonists which have a similar spectrum of pharmacological effects, is one of the promising strategies in the treatment of cardiovascular diseases.Materials and Methods. The study was carried out on 68 C57Bl/6J male mice. Atherosclerosis was simulated in transgenic animals with an endotheliospecific knockdown of the Polg gene by simulating a balloon injury and keeping on a Western diet. Then, the studied drugs were injected once every 3 days at the dose of 20 μg/kg for 27 days. On the 28-th day, the animals were euthanized and the area of atherosclerotic plaques was assessed. The gene expression associated with the processes of inflammation, antioxidant protection, apoptosis, and angiogenesis was also determined in the aortic tissues. In addition, the endothelium protective effect of peptides on primary cultures of endothelial cells of wild and transgenic Polg-D257A mice was studied.Results. No statistically significant effect of drugs on the area of lipid infiltration have been found. However, the studied peptides have significantly reduced the expression of proinflammatory genes (iNos, Icam1, Vcam1, Sele, Il6, Tnfa), the genes associated with angiogenesis (Vegfa, Kdr, and Hif1a), the expression of proapoptic factors; they decreased the Bax/Bcl-2 ratio by more than 1.5 times. In addition, when supplemented with H2 O2  in vitro, peptides dose-dependently increased endothelial cell survival.Conclusion. The erythropoietin-based peptides can be used to improve the functional state of the vascular wall against the background of atherosclerotic lesions and have a depressing effect on pathobiological processes associated with a mitochondrial dysfunction. In addition, the studied peptides have a significant endothelial protective effect in the induction of oxidative stress in vitro.